KARAKTERISTIK DAN UJI POT ORGANIK BERBAHAN DASAR LIMBAH KULIT GALAM (Melaleuca cajuputi) DAN ENCENG GONDOK (Eichornia crassipes) SEBAGAI PENGGANTI POLYBAG - Noor Mirad Sari; Violet Violet; Khairun Nisa; Shinta Ajar (Lambung Mangkurat University-Indonesia, 2021)
The forestry and plantation sectors till now, the mass supply of seeds still using polybags made from plastic. The purpose of the study was to examine the physical characteristics and test the organic pots based on waste from galam skin and water hyacinth as well as to find out the best basic ingredients for making organic pots. The research method used was Completely Randomized Design (CRD) with 5 treatments and 3 replications. The results of organic pot testing for water content ranged from 4.2133 – 6.033%, all treatments met the SNI standard 03-2105-2006 (<14%). The range of water absorption values is 97.9981 – 176.2218% and the SNI 03-2105-2006 standard does not require water absorption values. Density values ranged from 0.3584 – 0.8767 gr/cm3, A, C, D, E treatments were included in the SNI 03-2105-2006 standard. The best treatment of organic pot water content was in treatment A (100% galam peel waste), water absorption was found in treatment E (100% water hyacinth) and the best density was found in treatment E (100% water hyacinth. Results of organoleptic test of organic pots Based on the preference for color and texture, the highest was found in treatment A (100% galam bark waste) with a very hard texture and blackish color